22. SURGICAL TREATMENT OF PATHOLOGICAL FRACTURES OF THE PROXIMAL FEMUR DUE TO OSTEOPETROSIS DISEASE: CASE REPORT AND LITERATURE REVIEW (Vietnam Journal of Community Medicine, 2025)
Osteopetrosis is a rare hereditary disease which is characterized by increased bone density. We report 3 cases of pathological fractures of the proximal femur were treated by operation at Bone and Joint Pathology Department in Hospital for Traumatology and Orthopaedics at Ho Chi Minh city. All 3 cases of proximal femur fractures were surgically fixed with a locking plate and screw. The results of bone healing and function were good, with an average healing time of 1 year.
Keywords: Viral encephalitis; Japanese encephalitis; Herpes simplex virus; cerebrospinal fluid.